2020
DOI: 10.3389/fimmu.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation Is Associated With Mortality in Patients With Necrotizing Soft-Tissue Infections—A Prospective Observational Study

Abstract: Citation: Kristensen MK, Hansen MB, Madsen MB, Hansen CB, Pilely K, Hyldegaard O and Garred P (2020) Complement Activation Is Associated With Mortality in Patients With Necrotizing Soft-Tissue Infections-A Prospective Observational Study. Aim: We assessed whether different complement factors and complement activation products were associated with poor outcome in patients with necrotizing soft-tissue infection (NSTI). Methods: We conducted a prospective, observational study in an intensive care unit where treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We evaluated different complement activation products at the C4, C3, and terminal levels. Earlier, in a smaller part of the present cohort, we have demonstrated that consumption of molecules, particularly from the lectin pathway and other downstream molecules, were associated with increased risk of death, contrasting to patients capable of maintaining high circulating levels of complement molecules [19, 20]. Of particular relevance, we have previously reported high C4 to be associated with improved survival [20], and in that context, we demonstrated in the present and larger cohort a high C4d to be associated with increased mortality.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We evaluated different complement activation products at the C4, C3, and terminal levels. Earlier, in a smaller part of the present cohort, we have demonstrated that consumption of molecules, particularly from the lectin pathway and other downstream molecules, were associated with increased risk of death, contrasting to patients capable of maintaining high circulating levels of complement molecules [19, 20]. Of particular relevance, we have previously reported high C4 to be associated with improved survival [20], and in that context, we demonstrated in the present and larger cohort a high C4d to be associated with increased mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Earlier, in a smaller part of the present cohort, we have demonstrated that consumption of molecules, particularly from the lectin pathway and other downstream molecules, were associated with increased risk of death, contrasting to patients capable of maintaining high circulating levels of complement molecules [19, 20]. Of particular relevance, we have previously reported high C4 to be associated with improved survival [20], and in that context, we demonstrated in the present and larger cohort a high C4d to be associated with increased mortality. Interestingly, we have earlier found a high level of C3bc at admission to be associated with increased mortality, but this was not mirrored in the present analyses, showing no statistical association to death.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The development of rapid diagnostic tools for NSTI, such as levels of disease-associated biomarkers, to support clinical decisions could increase the accuracy of early diagnosis, leading to swifter surgical exploration and treatment only when clinically indicated. However, to date, there are only a few studies of molecular biomarkers in NSTIs (22,(28)(29)(30)(31)(32), and these are limited to analyses of only a few markers. The comprehensive multiplex analysis of 36 analytes conducted here revealed, as expected, a greater systemic inflammatory response in NSTI patients than in noninfected patients (surgical controls).…”
Section: Discussionmentioning
confidence: 99%
“…The anaphylatoxin production in particular seems to be associated with a bad outcome [55][56][57][58][59][60][61][62]. In patients suffering from necrotizing soft tissue infections with or without septic shock, complement activation was evident and high levels of the C4c/C4 ratio, C3bc, and the C3bc/C3 ratio were associated with an enhanced long-term mortality [63]. Patients with severe tissue trauma also exhibited enhanced C3a and C5a plasma levels especially when they developed septic complications [64,65].…”
Section: Translational Approaches Of Complement Monitoring and Modulation In Clinical Sepsismentioning
confidence: 99%